Can’t find the antidote: A root cause analysis - Abu Esba, Laila Carolina; Mardawi, Ghada; Al Deeb, Mohammad (Frontiers in Pharmacology, 2022)
Background: In a series of cases that came to be recognized as a national methanol outbreak, the incidence of delay in allocation and treatment with the antidote fomepizole is described with aim of sharing a learning experience. Method: A team of 16 members was formed to conduct a Root Cause Analysis (RCA), which included multiple individual interviews with the stakeholders and inspection visits to the area. Results: Root causes: The restocking process was unclear and inconsistent and specifically lacked a restocking policy for antidotes, inappropriate labeling and area design, and a sound-alike between fomepizole and omeprazole. Contributing factors included: unsuitable restocking practice and lack of training in using the pharmaceutical electronic inventory system. Corrective actions were recommended and implemented. Conclusion: Management of antidotes in large healthcare systems requires a team effort to ensure appropriate and timely availability in emergency poisoning cases. This RCA identified important areas for improvement that could be insightful to other institutions in preventing similar vulnerabilities and is unique in describing the details of system improvements that can have a large impact on patient safety.